The Use of E-commerce and QRIS as Digital Payment Solutions to Enhance Sales Performance in MSMEs in West Java - Darlene Gabriella S.; Lia Yuldinawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to examine the impact of digitalization on the performance of MSMEs, focusing on how the adoption of e-commerce and QRIS affects the sales performance of MSMEs in West Java through competitive advantage. The study also explores the potential of MSMEs in the current era of digitalization and provides recommendations based on the obtained results to support the growth of MSMEs on a national scale. To achieve these objectives, the study employs a quantitative analysis method. The quantitative component focuses on statistical analysis of the e-commerce and QRIS utilization among West Java MSMEs, MSMEs' sales performance, and MSMEs' competitive advantages in digitally active MSMEs. The analysis method in this study uses non-probability sampling and collected data from 400 MSME owners/actors in West Java. The data was collected using a survey and conducted in a non-contrived setting. This study uses SPSS version 29 for data processing, including validity testing, reliability testing, descriptive analysis, and three classical assumption tests, including normality, multicollinearity, and heteroscedasticity. In this study, a t-test, path analysis, and Sobel test were carried out on hypothesis testing. The study highlights that MSMEs that have successfully integrated digital technologies experienced improved business performance, including increased sales, expanded customer base, and improved operational efficiency. This study also proves the mediating role of competitive advantage which significantly and positively affects sales growth in MSMEs. The results of this study indicate the influence of partial mediation, namely complementary mediation.